Synthesis of pretubulysin-derivatives via the TubUgi-approach1. Issue 21 (7th June 2015) - Hoffmann, Judith; Gorges, Jan; Junk, Lukas; Kazmaier, Uli
<x xml:space="preserve">Abstract</x> The Ugi reaction is a powerful tool for the synthesis of (pre)tubulysin derivatives, allowing the introduction of functionalized side chains.